PENINGKATAN KUALITAS PENDIDIKAN ANAK DAN KESADARAN LINGKUNGAN DI DESA WISATA BAWOMATALUO MELALUI PROGRAM KKN - Fendianus Laowo; Meydian Angelin Solomasi Gowasa; Elman Kasih Laia; Daria Dewi Sinta Ndruru; Elson Joice Zagoto; Damian Histori Faforitman Harefa; Rantis Laia; Festiana Laia; Renita Restuti Ndruru; Wilhelmina Duha; Alber Juang Sihura; Anskaria Simfrosa Gohae (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Bawomataluo Village in South Nias Regency is known as a cultural tourism village, rich in tradition and distinctive traditional house architecture. Despite its great potential, the community faces challenges in children's education and environmental awareness. The Community Service Program (KKN) of Nias Raya University was implemented with a Private Tutoring program for children as its main initiative to enhance academic understanding, basic skills, and self-confidence. Supporting programs such as Saving Education for Children, the implementation of Sapta Pesona (the Seven Charms of Tourism), the creation of waste bins and broomsticks from coconut fronds, and a Children's Event, aimed to reinforce educational outcomes and build environmental awareness. The implementation results showed an increased enthusiasm for learning, the growth of saving awareness, and enhanced community concern for environmental cleanliness. This program demonstrates the integration of education and environmental empowerment, which supports the development of Bawomataluo Village as a sustainable cultural tourism destination.